Studies on rabbit meat quality recovered from pasteurellosis - Ibrahim I.S.; Gergis S.M.; Khodier M.H.; Hamdy M.M.; Abd El Latif H.A. (Rabbit production in hot climates, 1994)
This work was planned to study the effect of pasteurellosis on rabbit meat quality. The slaughter data in both control and experimentally infected rabbits were calculated and showed significant differences all over the period of the experiment, between the two groups. The living body weight, shoulder and thorax, lions and flank, rump and thigh; giblet weight and dressing percentage decreased significantly in recovered rabbit in comparison with control. Also, sensory evaluation test revealed a highly significant difference in all testing items between control and recovered rabbits 2 days post treatment. The estimation of the main chemical composition of rabbit meat showed non significant differences in such components except the fat percentage that showed significant decreased on the 2nd and 5th day post infection and treatment. Evaluation of the economic effect of pasteurellosis in rabbits was also discussed.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)